Comparison Between Early and Delayed Removal of Urethral Catheter in Patients with Elective Cesarean Section - Din, Sadia; Habib, Laila; Liaqat, Nazia (Indus Journal of Bioscience Research, 2025)
Background: Urinary catheterization after elective cesarean section is routine; nevertheless, when to remove the catheter might affect postoperative results. The early removal of the catheter is considered to minimize adverse consequences such as hematuria and urinary tract infections. Objective: To compare the frequency of adverse outcomes of early and delayed removal of the urethral catheter in patients with elective cesarean section at Lady Reading Hospital Peshawar. Study Design: Randomized controlled trial. Duration and Place of Study: This study was conducted from January 2024 to July 2024 at the Department of Obstetrics and Gynaecology, LRH Peshawar. Methodology: A total of 384 patients aged 18–40 years, with singleton pregnancies and a gestational age between 36 and 41 weeks, were included. The participants were randomly assigned to either the early removal group (catheter removed 2 hours postoperatively) or the delayed removal group (catheter removed 12 hours postoperatively). Adverse outcomes, specifically fever (defined as a body temperature >38°C) and hematuria (defined as ≥5 RBCs per high-power field in three consecutive centrifuged specimens), were monitored throughout the patients' hospital stay. Results: The mean age of participants was similar between groups. The early removal group had a fever incidence of 2.6%, while the delayed removal group had an incidence of 5.2%, but the difference was not statistically significant (p=0.292). Hematuria was significantly more frequent in the delayed removal group (50%) compared to the early removal group (21.4%) with a p-value of <0.001, indicating a strong association between delayed catheter removal and hematuria. Conclusion: Early removal of the urinary catheter following elective cesarean section significantly reduces the risk of hematuria, with no significant impact on the occurrence of fever.